Hardness and microstructure of FDM 3D printed parts using self-made PLA-brass filaments - Darsin, Mahros; Ramadhan, Ivan Fadilla; Sumarji, Sumarji; Dwilaksana, Dedi; Sutjahjono, Hary; Ales, Steve Korakan (SINERGI, 2024)
Technological advancements in the industrial sector have led to rapid developments in 3D printing technology, enabling the creation of three-dimensional prototype models. Various filaments, including polyethylene terephthalate glycol, nylon, and polylactic acid, have been widely adopted in the industry. However, filaments composed of metal mixtures are relatively scarce in Indonesia, primarily available only through select online shops worldwide. The production and sale of such filaments present lucrative opportunities within the manufacturing industry. In this research, an experimental study was conducted to examine the hardness of test specimens fabricated using PLA-brass filament. The objective was to identify the optimal hardness value of the specimens. The study focused on three key parameters: nozzle temperature, layer height, and print speed, each at two different levels. The Taguchi L4(2³) experimental design was employed, along with S/N ratio and ANOVA analysis, to evaluate the results. The findings revealed that specific combinations of parameters yield favorable hardness values, as determined by the Taguchi Method. The optimal set of parameters for achieving good hardness values was determined to be a nozzle temperature of 230°C, a layer height of 0.2 mm, and a print speed of 40 mm/s. These results enhance the understanding of PLA-brass filament properties and facilitate the utilization of 3D printing technology in the manufacturing industry.